A díade treinador personalizado online e cliente: análise das relações interpessoais - Isler, Gustavo Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Communication and interpersonal relationships mediated by technology are so complex and rich in detail and shade as stablished in the presential context. Lot of aspects of communication and interpersonal distance relationship were postulated by the scientific literature, but scant, and why not practically nonexistent, are those who have sought to understand, as well as the intended purpose of this study, the context of Online Personal Training (OPT) and the relations between personal trainers and clients during this contemporary training method. Focusing on these objectives has been proposed the method based on a quantitative and qualitative research to explore and describe the perceptions of seven online personal trainers and eight clients. Sociodemographic and specific questionnaires made available via Google Docs®, and semi-structured interviews implemented through Whatsapp® application and chat Facebook® allowed data collection. Every procedure was authorized by the Ethics Committee on Human Beings Research of the IB of UNESP from Rio Claro/SP, which was based on ethical standards established by Resolution 466/12 of the CNS. The data interpretation, achieved by content analysis of participants' responses was organized on the following topics: perceptions of the participant involvement with the OPT process; technological tools used by participants during the OPT; the participants' perceptions about their communication and interpersonal skills through OPT. The review process demonstrated that participants have little experience with OPT and perceive as an effective training method. The coaches reasons to start in the OPT were interested in increasing the financial gains, the number of customers and meeting the needs of the same. For clients, the competence of the coach and the unavailability to adhere to face-to-face training was the main reasons. The technological tools most commonly used for communicating are Whatsapp®, e-mail...

A comunicação e o relacionamento interpessoal quando mediados pela tecnologia são tão complexos e ricos em detalhes e nuances quanto os estabelecidos no âmbito presencial. Muitos aspectos sobre a comunicação e a relação interpessoal à distância foram postulados pela literatura científica, mas escassos, e por que não afirmar praticamente inexistentes, são aqueles que buscam compreender, assim como pretende o objetivo deste estudo, o contexto do Treinamento Personalizado Online (TPO) e as relações estabelecidas entre treinadores personalizados e clientes durante este método de treinamento contemporâneo. Com foco em tais objetivos foi proposto o método fundamentado por uma pesquisa quanti-qualitativa destinada a explorar e descrever as percepções de sete treinadores personalizados online e oito clientes. Questionários sociodemográficos e específicos, disponibilizados via Google Docs®, e entrevistas semiestruturadas concretizadas através do aplicativo Whatsapp® e do bate-papo do Facebook® permitiram a coleta dos dados. Todo procedimento foi autorizado pelo Comitê de Ética em Pesquisa em Seres Humanos do IB da UNESP de Rio Claro/SP, o qual se pautou nos padrões éticos estabelecidos pela Resolução 466/12 do CNS. A interpretação dos dados, concretizada através da análise do conteúdo das respostas dos participantes, foi organizada nos seguintes temas: as percepções sobre o envolvimento dos participantes com o processo de TPO; as ferramentas tecnológicas utilizadas pelos participantes durante o TPO; as percepções dos participantes sobre sua comunicação e relacionamento interpessoal através do TPO. O processo de análise demonstrou que os participantes têm reduzida experiência com o TPO e o percebem como um método eficiente. Os motivos dos treinadores para iniciar no TPO foram o interesse em aumentar os ganhos financeiros, o número de clientes e o atendimento das necessidades dos mesmos. Para os clientes...
Keywords: Physical education and training; Educação fisica; Relações humanas; Preparadores físicos pessoais; Comunicação